Feasibility, effectiveness, and safety of edoxaban administration through percutaneous endoscopic gastrostomy: 12-months follow up of the ORIGAMI study - Cappannoli, Luigi; Laborante, Renzo; Galli, Mattia; Canonico, Francesco; Ciliberti, Giuseppe; Restivo, Attilio; Princi, Giuseppe; Arcudi, Alessandra; Sabatelli, Mario; De Cristofaro, Raimondo; Crea, Filippo; D’Amario, Domenico (Frontiers in Cardiovascular Medicine, 2022)
Background and aims Edoxaban proved to be safe and effective also in fragile patients, but its administration through percutaneous endoscopic gastrostomy (PEG) has not been previously investigated. The purpose of this study was to evaluate the feasibility and the preliminary safety and efficacy profiles of edoxaban administered via PEG in patients with an indication for long-term oral anticoagulation. Methods ORIGAMI was a prospective, single-arm, observational study (NCT04271293). Patients with PEG and an indication for long-term anticoagulation were prospectively enrolled. Crushed edoxaban at approved doses was administered via PEG. The primary endpoint was the composite of cardio-embolic events consisting of ischemic stroke, systemic embolism, or symptomatic deep venous thrombosis/pulmonary embolism (DVT/PE). Secondary endpoints were the number of bleeding events and edoxaban plasma concentrations at steady state. We here report the 12-month results. Results A total of 12 patients were enrolled. The main indication for PEG implantation was amyotrophic lateral sclerosis (10/12). The primary endpoint of cardio-embolic events did not occur in any patients at 12 months. All patients were in the therapeutic range of steady-state edoxaban plasma levels. Three minor bleedings were observed, while no major bleedings occurred during the observational period. A total of five patients died. All deaths were from non-cardiovascular causes and were consistent with the natural history of the pre-existing severe disease. Conclusion Our study suggests that edoxaban administration via PEG is feasible and appears safe and effective in fragile, comorbid patients, resulting in therapeutic plasma concentrations of edoxaban. Clinical trial registration [ClinicalTrials.gov], identifier [NCT04271293].